THE POLITICIZATION OF ETHNIC IDENTITY IN THE MODERN WORLD: PROBLEMS AND INSTITUTIONAL SOLUTIONS - Panov, P.V. (Perm Federal Research Centre Journal, 2015)
One of the basic trends of contemporary political development is a politicization of ethnicity, which gives rise to some problems and sometimes causes sharp conflicts in universalistic in their form nation-states. The paper discusses the conceptual framework for the analysis of these processes. Some basic concepts - identity, ethnicity, and the politicization of ethnic identity - are examined. Two main approaches (accommodation and integration) to the question of how to deal with problems arising from the politicization of ethnic identity are discussed. Each of them offers its own set of institutional decisions. Overview of solutions presented in this paper allows to make a conclusion that each of the approaches has some advantages and disadvantages. As a result, they produce divergent effects.